1, 8‐Naphthalimide Derivative Dyes with Large Stokes Shifts for Targeting Live‐Cell Mitochondria. (26th July 2016) - Zhang, Liqiang; Su, Fengyu; Kong, Xiangxing; Lee, Fred; Sher, Steven; Day, Kevin; Tian, Yanqing; Meldrum, Deirdre R.
Abstract: An ideal fluorescent dye for staining cell organelles should have multiple properties including specificity, stability, biocompatibility, and a large Stokes shift. Tunable photophysical properties enable 1, 8‐naphthalimide to serve as an excellent fluorophore in biomedical applications. Many naphthalimide derivatives have been developed into drugs, sensors, and other dyes. In this study, a series of 1, 8‐naphthalimide derivatives targeting live cell mitochondria were synthesized. Among these probes, Mt‐4 was characterized as the best one, with highly specific mitochondrial localization, low cytotoxicity, and a large Stokes shift. More importantly, Mt‐4 stood out as a potential mitochondrial dye for living‐cell experiments involving induced mitochondrial stress arising from the treatments because Mt‐4 shows enhanced fluorescence in mitochondrial stress situations. Abstract : A fluorescent probe for mitochondria : A series of 1, 8‐naphthalimide derivatives targeting live cell mitochondria were synthesized. Among these probes, Mt‐4 is the best, with highly specific mitochondrial localization, low cytotoxicity, and a large Stokes shift. It is a potential mitochondrial dye for living‐cell experiments involving mitochondrial stress arising from the conditions.